2017
DOI: 10.1128/mmbr.00015-17
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Understanding of Bacterial Polysaccharide Monooxygenases

Abstract: Bacteria have long been known to secrete enzymes that degrade cellulose and chitin. The degradation of these two polymers predominantly involves two enzyme families that work synergistically with one another: glycoside hydrolases (GHs) and polysaccharide monooxygenases (PMOs). Although bacterial PMOs are a relatively recent addition to the known biopolymer degradation machinery, there is an extensive amount of literature implicating PMO in numerous physiological roles. This review focuses on these diverse and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 150 publications
(192 reference statements)
0
36
0
Order By: Relevance
“…The high prevalence of lpmO genes in pathogenic bacteria and their increased expression in multiple omics-type driven analyses in the context of host-pathogen interactions (reviewed in refs. 16 , 17 ) suggest a potential biological function during infection. Our finding of the decline in bacterial survival in vivo in a murine model of PA systemic infection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of lpmO genes in pathogenic bacteria and their increased expression in multiple omics-type driven analyses in the context of host-pathogen interactions (reviewed in refs. 16 , 17 ) suggest a potential biological function during infection. Our finding of the decline in bacterial survival in vivo in a murine model of PA systemic infection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, CHB1 acted as a facilitator of the remodeling of chitin filaments and initiator of contacts between Streptomyces cells and fungal hyphae, then promoting a more efficient hydrolysis of chitin in the fungal cell wall (Siemieniewicz and Schrempf 2007 ). With the discovery of the enzymatic activity of these proteins, now called lytic polysaccharide monooxygenases (LPMOs) (Vaaje-Kolstad et al 2010 ; reviewed by Agostoni et al 2017 ), it was shown that the effects observed both in vitro and in vivo were not only due to the binding of LPMOs to chitin chains and fungal cell walls but essentially to their capacity to cleave chitin chains using a novel, oxidative mechanism. Actinobacterial LPMOs belong to family AA10, grouping enzymes acting either on chitin or cellulose.…”
Section: Overview Of Actinobacterial Enzymes Involved In Chitinolysismentioning
confidence: 99%
“…This disruptive action boosts the depolymerizing action of glycoside hydrolases 1,2,5 . LPMOs, classified today in families 9-11 and 13-16 of the auxiliary activities (AA) in the Carbohydrate Active enZymes database 9 , are ubiquitous enzymes with key roles in biological conversion of biomass by fungi and bacteria, but also with suggested roles in microbial pathogenicity [10][11][12] . LPMOs contribute to the efficiency of modern commercial cellulase cocktails used at industrial scale 13,14 .…”
mentioning
confidence: 99%